MAJOR FLAWS IN TECHNIQUE OF INTRAMUSCULAR INJECTIONS: Technique of Intramuscular Injections - Waleem, Maj Sheikh Saadat Ullah; Khan, Yasser Saeed; Tarar, Humayun Munir (Pakistan Armed Forces Medical Journal, 2013)
Objectives: To identify the major flaws in technique of administering intramuscular injections by our health care professionals and to suggest improvements based upon a scientific study. Design: Cross sectional (Jan-Feb, 2011). Place: Combined Military Hospital Sargodha, Pakistan Air Force Hospital Sargodha, Pakistan Air Force Hospital Mianwali. Patients and Methods: All staff involved in administration of IM injection to the patients. A detailed questionnaire was required to be filled in front of an observer and submitted. Injection sites were required to be marked on diagrams. The data were analyzed by SPSS 17. Results: Major flaws were identified in the technique of administration of IMI.